Computational Analysis on Plug-in Hybrid Electric Motorcycle Chassis - Teoh, S. J.; R. A., Bakar; Gan, Leong Ming (2013)
Plug-in hybrid electric motorcycle (PHEM) is an alternative to promote sustainability of energy and lesser emission. However, the PHEM overall system packaging is constraint by limited space in a motorcycle chassis. In this paper, a chassis applying the concept of a Chopper is analysed to apply in PHEM. The chassis 3dimensional (3D) modeling is built with CAD software. The PHEM power-train components and drive-train mechanisms are intergraded into the 3D modeling to ensure the chassis provides sufficient space. Besides that, a human dummy model is built into the 3D modeling to ensure the rider’s ergonomics and comfort. The chassis 3D model is then undergoing stress-strain simulation. The simulation predicts the stress distribution, displacement and factor of safety (FOS). The data are used to identify the critical point, thus suggesting the chassis design is applicable or need to redesign/modify to meet the require strength. Critical points mean highest stress which might cause the chassis to fail. This point occurs at the joints at triple tree and bracket rear absorber for a motorcycle chassis. As a conclusion, computational analysis predicts the stress distribution and guideline to develop a safe prototype chassis.